Synergistic effect of Jatropha curcas seed oil and sodium tetraborate treatment on wood resistance to fungal attacks: case of Ayous (Triplochiton scleroxylon), a high value commercial wood species in tropical Africa. Issue 3 (4th May 2022) - Georges, Bessike Josias; Evariste, Fongnzossie; Achille, Biwolé; Joseph, Zobo Mfomo; Moise, Ntah Ayong; Dieudonné, Abessolo; Lambert, Sameza Modeste; Patrick, Akono Ntonga
ABSTRACT: This study evaluated the synergistic effect of Jatropha curcas seed oil and sodium tetraborate as a preservative of Triplochiton scleroxylon wood against four selected fungi species. The experimental design consisted of seven treatments with different concentrations of sodium tetraborate and J. curcas seed oil at a concentration of 4000 μg/l in all treatments, except the control. Mycelia growth of the different fungi was measured daily in vitro for 4 days. Wood blocks of T. scleroxylon of 25 × 15 × 5 mm with 25% moisture content each were exposed to the 4 fungi for 16 weeks and weight loss was measured. As compared to the control, all the treatments influenced mycelia growth. Treatment with Jatropha seed oil was effective in reducing significantly the mycelia growth ( P < .05). The higher the sodium tetraborate concentration, the lower the mycelium growth. Untreated samples gave highest weight loss of 25.15 ± 0.01% with Scopulariopsis sp ., while treated samples yielded the lowest weight loss with values of 0.74 ± 0.01, 0.33 ± 0.01, 0.32 ± 0.01, and 0.07 ± 0.06 with Scopulariopsis sp., Poria placenta, Penicilium sp . and Mucor graphium, respectively . The combination of J. curcas seed oil and sodium tetraborate is a potential eco-friendly wood protectant against fungal attacks.